How Can Diet Influence the Risk of Stroke?. (30th May 2012) - Medeiros, Fernanda; Casanova, Marcela de Abreu; Fraulob, Julio Cesar; Trindade, Michelle
Abstract : Cerebrovascular diseases are the second cause of mortality in the world, and hypertension is considered a main risk factor for occurrence of stroke. The mechanisms responsible for the increased stroke risk remain unclear. However, dietary interventions have been applied in the management and treatment of their risk factors, which include increased blood pressure levels, obesity, diabetes, and dyslipidemia. Further studies should be conducted to assess the effects of carotenoids, flavonoids, n-3 polyunsaturated fats, and lower salt and high glycemic index intake in risk of stroke.